Role of Interleukin-1 Signaling in a Mouse Model of Kawasaki Disease–Associated Abdominal Aortic Aneurysm. Issue 5 (May 2016) - Wakita, Daiko; Kurashima, Yosuke; Crother, Timothy R.; Noval Rivas, Magali; Lee, Youngho; Chen, Shuang; Fury, Wen; Bai, Yu; Wagner, Shawn; Li, Debiao; Lehman, Thomas; Fishbein, Michael C.; et al.
Abstract : Objective—: Kawasaki disease (KD) is the most common cause of acquired cardiac disease in US children. In addition to coronary artery abnormalities and aneurysms, it can be associated with systemic arterial aneurysms. We evaluated the development of systemic arterial dilatation and aneurysms, including abdominal aortic aneurysm (AAA) in the Lactobacillus casei cell-wall extract (LCWE)–induced KD vasculitis mouse model. Methods and Results—: We discovered that in addition to aortitis, coronary arteritis and myocarditis, the LCWE-induced KD mouse model is also associated with abdominal aorta dilatation and AAA, as well as renal and iliac artery aneurysms. AAA induced in KD mice was exclusively infrarenal, both fusiform and saccular, with intimal proliferation, myofibroblastic proliferation, break in the elastin layer, vascular smooth muscle cell loss, and inflammatory cell accumulation in the media and adventitia. Il1r −/−, Il1a −/−, and Il1b −/− mice were protected from KD associated AAA. Infiltrating CD11c + macrophages produced active caspase-1, and caspase-1 or NLRP3 deficiency inhibited AAA formation. Treatment with interleukin (IL)-1R antagonist (Anakinra), anti–IL-1α, or anti–IL-1β mAb blocked LCWE-induced AAA formation. Conclusions—: Similar to clinical KD, the LCWE-induced KD vasculitis mouse model can also be accompanied by AAA formation. Both IL-1α and IL-1β play a key role, and use of an IL-1R blocking agent that inhibits both pathways may be a promising therapeutic target not only for KD coronary arteritis, but also for the other systemic arterial aneurysms including AAA that maybe seen in severe cases of KD. The LCWE-induced vasculitis model may also represent an alternative model for AAA disease. Abstract : Supplemental Digital Content is available in the text.